Protanopia en paciente masculino de 22 años de edad. - Aguilar Galeas, Diana Priscila (2022)
Protanopia is the optical deficiency caused by the absence of the cones, the person suffering from this rare condition has a loss of sensitivity to light at the red end of the color spectrum, particularly that it derives from color blindness, it can be hereditary from parents to children. through the chromosomes. Worldwide, Protanopia develops more in males by 8% (640 million approx.) than in females with 0.5% (40 million approx.). The present case study was carried out on a 22-year-old male patient, who came to the clinic indicating that he had difficulty identifying a certain color, in addition he had a headache in the occipital part, visual fatigue in both eyes, blurred vision when observing a color. remote object. Optometric examinations were carried out, such as the measurement of visual acuity both from a distance and from near with and without correction, eye fundus, Ishihara test and Farnsworth test, which allowed us to observe that our patient presents a refractive error and a certain color vision deficiency. The treatment provided was optical correction through the use of glasses with negative spherical lenses and the additional application of a green color filter. In conclusion, a visual control will be improved every 6 months to find out how the contrast of red objects has improved and to see if there are changes in its graduation and make the proper correction for better visual acuity.